Improvement of The Methodology for Inventorying Degraded Reclaimed Lands - Atakulov To'xtamurod Umarovich (American Journal Of Agriculture And Horticulture Innovations, 2025)
The proposed methodology for increasing the efficiency of monitoring degraded reclaimed lands defines a unified approach and structure for conducting agricultural land monitoring in the country.